The moderating role of corporate social responsibility in the association of internal corporate governance and profitability; evidence from Pakistan - Jihai, Lu; Javeed, Sohail Ahmad; Latief, Rashid; Tao, Jiang; Tze, San Ong (MDPI AG, 2021)
At present, climate and other environmental problems are arising because of the development of the industrial sector at a large level. The industrial sector is supposed to be a major cause of climate change problems that lead to global warming. Therefore, corporate social responsibility (CSR) with the help of corporate governance is an imperative approach to control these social problems. Consequently, in the context of the organizational and management theory, agency theory, and the stakeholder theory, this study focuses on important factors of internal corporate governance such as chief executive officer (CEO) power, the board size, independence, ownership concentration, managerial ownership, and audit quality for improving the profitability of firms. Moreover, this study considers corporate social responsibility as a controlling and moderating factor for firm performance and internal corporate governance. We employed ordinary least square (OLS) for endogeneity testing, fixed effect (FE), generalized method of moments (GMM), and feasible generalized least square (FGLS) on data of Pakistani firms for the period of 2010–2019. The results of this study demonstrate the following outcomes: firstly, all internal corporate governance factors are positively linked with firm performance; secondly, corporate social responsibility (CSR) is the most valuable tool for improving profitability. Importantly, this study suggests that all internal corporate governance factors are positively linked with firm performance because of the interactive role of corporate social responsibility (CSR). This study practically contributes to the literature by suggesting the imperative role of corporate social responsibility (CSR) for internal corporate governance, which may help to reduce climate and social problems.